The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1149/1.2355757
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Stress and Defect Formation in Device Processing

Abstract: In this work we address the problem of estimating the mechanical stress and the related risk of crystal defect generation in a complex device process. The validity of numerical calculations of the mechanical stress developed in the device process flow is assessed by comparing the simulation results with the electrical measurements of test structures designed to monitor the dislocations formation and of other silicon strain sensitive structures. The results show that based upon numerical calculations it is poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…due to the volume expansion of SiO 2 compared with Si, thermal stresses, created during fast cooling of the wafers after field oxidation 90 were shown to play an important role. In many cases, the stress was high enough to exceed the yield stress of silicon, leading thus to the creation of extended defects, [94][95][96][97][98][99] which were penetrating the depletion region and, hence, cause a reduction of the generation lifetime s g in Eq. 1.…”
Section: Introductionmentioning
confidence: 99%
“…due to the volume expansion of SiO 2 compared with Si, thermal stresses, created during fast cooling of the wafers after field oxidation 90 were shown to play an important role. In many cases, the stress was high enough to exceed the yield stress of silicon, leading thus to the creation of extended defects, [94][95][96][97][98][99] which were penetrating the depletion region and, hence, cause a reduction of the generation lifetime s g in Eq. 1.…”
Section: Introductionmentioning
confidence: 99%
“…As previously mentioned, in process flows with a STI structure the mechanical stress is developed during the thermal oxidations that follow the STI formation (8). In addition, the deeper the trench, the higher the stress-related dislocation formation probability is (17). Numerical simulations showed that the silicon compression is maximum at the top corner of the active area.…”
Section: Ecs Transactions 50 (5) 303-317 (2012)mentioning
confidence: 99%
“…Electrical measurements. Dislocations in transistors are electrically active if they connect the source and the drain regions (8,10,17,21). In this case, the dislocation usually acts as a source-to-drain conductive path, because of the anomalous dopant diffusion from the source and drain regions along the dislocation.…”
Section: Structure Descriptionmentioning
confidence: 99%
See 1 more Smart Citation